SELECTIVE FRACTIONATION OF PALM STEARIN TO PRODUCE PPP AND POP-RICH FATS - Kamilah Abidin, Aisyah
Palm oil is one of the main commodity crops which has an important role in Indonesia's economic activities. The palm oil production continues to increase every year. Palm oil is processed into RBDPO (Refined Bleached Deodorized Palm Oil) which is then separated to produce two types of fractions, solid (PS, palm stearin) and liquid (PO, palm olein). PS contains the main triglycerides in the form of PPP and POP. PPP and POP are special triglycerides because they can be used as raw material for high-fat feed for Ruminantia and functional food products (structured lipids). The various types of structured lipids that exist are human milk breast substitute (ASI) and cocoa butter equivalent (CBE). In this research, PPP and POP were obtained from PS as raw material with a twostages solvent fractionation method. The effect of the use of solvents is seen by varying the ratio of PS to solvents in a ratio of 1: 8; 1:10; and 1:12 w/v. The first stage fractionation was carried out at temperatures of 25?C, 38?C and 45?C to obtain solid and liquid fractions. The liquid fraction will go through a second stage fractionation process to produce a solid fraction. The solids produced from each stage were analyzed to determine the effect of the use of the solvent and its fractionation temperature on the yield and quality of the solids. An increase in the ratio of PS to solvent and an increase in fractionation temperature tended to result in a decrease in the yield of solid fraction I, while solid fraction II increased. Solids from the first stage fractionation produced a melting temperature in the range 56?C-68?C and solid fraction II produced a melting temperature in the range 51?C-64?C. From these results, solid fraction I can be said to be the rich fraction of PPP, while the second stage fractionation has not succeeded in producing POP rich fraction.